Penerapan Good Corporate Governance, Dampaknya Terhadap Prediksi Financial Distress pada Sektor Pertanian dan Pertambangan - Sutedjo, Marcella (Business Accounting Review, 2013)
This study aimed to know the influence of Good Corporate Governance to the financial distress prediction of companies in the agricultural and mining sectors listed in the Indonesia Stock Exchange in the period of 2004 to 2011. The independent variables used were GCG score with control variables including the net profit margin, debt to total assets ratio, and current ratio. The samples used in this study were 17 agricultural companies and 26 mining companies grouped into 30 healthy firms and 13 firms that experienced financial distress. The period used was three years before the company experienced financial distress and analyzed by using logistic regression. The study was divided into 3 models namely Model 1 (1 year prior to financial distress), model 2 (2 years before financial distress), model 3 (3 years prior to financial distress). The results showed that the variables that could predict were NPM (model 1), NPM and CR (model 2), while for the model 3 no variable was able to predict. The better model to predict was 1 year before the companies experienced financial distress.